A Case of Papillary Urothelial Neoplasm of Low Malignant Potential (PUNLMP) in Childhood - Reza Abbasion; Amir Jafarpisheh; Paria Dehghanian; Mahdi Mottaghi (Case Reports in Urology)
Urothelial carcinoma (UC) of the bladder is exceedingly rare in the pediatric population. It commonly presents as isolated hematuria. Considering the age group, the physician’s low index of suspicion causes a delay in diagnosis. We present a seven-year-old girl complaining of dysuria and painless, intermittent hematuria. She was misdiagnosed with urinary tract infection several times. Although the initial ultrasound showed no abnormality, the second ultrasound after one year detected the tumor. The confirmation and resection are simultaneously achieved by cystoscopy. We concluded that chemotherapy is unnecessary due to the tumor’s low-grade nature and the absence of detrusor involvement. One-year follow-up showed no relapse.